Kenya : A Policy Agenda to Restore Growth - World Bank (Washington, DC, 2013)
This Country Economic Memorandum (CEM) - the first since 1995 - is a contribution to the government's economic recovery strategy, and to its Poverty Reduction Strategy Paper (PRSP), being finalized. It examines Kenya's economic performance during the past decade, and identifies the structural weaknesses that have contributed to the decline in productivity, and the competitiveness of the economy during this period. It also recommends policy, and institutional reforms to revitalize economic growth, and to reduce poverty. The message from the CEM is a sober one: increased poverty is the legacy from almost two decades of slow growth; and, the burden of disease, particularly malaria and HIV/AIDS will constrain growth in the years to come. However, given the improved economic policy environment, the potential for economic growth is significantly better than the poor performance in the 1990s would indicate. But even in our high-case scenario Kenya is unlikely to reach the Millennium Development Goal of cutting in half by 2015 the proportion of Kenyans living in poverty in 1990. Reducing poverty will remain a tremendous challenge. The CEM is organized into six chapters. Chapter 1 reviews recent economic developments, and Kenya's integration with the world economy. Chapter 2 discusses trends in poverty, and focuses on the long term economic factors that affect productivity, and institutional effectiveness. Chapters 3-5 provide detailed analyses of the agricultural, manufacturing, and services sectors, identifying specific cross-sectoral issues, and, recommending policy, and institutional reforms to promote broad-based economic growth. Finally, chapter 6 discusses the investment climate, and its relationship to private sector investment.